Patterns of strain and the determination of the safe arc of motion after subscapularis repair—A biomechanical study. Issue 3 (18th September 2015) - Knesek, Michael; Brunfeldt, Alexander; Korenczuk, Christopher; Jepsen, Karl J.; Robbins, Christopher B.; Gagnier, Joel J.; Allen, Answorth A.; Dines, Joshua S.; Bedi, Asheesh
ABSTRACT: This study characterizes the strain patterns and safe arcs for passive range of motion (ROM) in the superior and inferior subscapularis tendon in seven cadaveric shoulders, mounted for controlled ROM, after deltopectoral approach to the glenohumeral joint, including tenotomy of the subscapularis tendon 1 cm medial to its insertion on the lesser tuberosity. The tenotomy was repaired with end‐to‐end suture in neutral rotation. Strain patterns were measured during passive ROM in external rotation (ER), ER with 30° abduction (ER+30), abduction, and forward flexion in the scapular plane (SP) before and after surgery. Percentages were calculated from 35 trials corresponding to five trials of each motion across seven specimens. With ER of 0−30°, 89% of trials of superior subscapularis tendon and 100% of trials of inferior subscapularis tendon achieved strains >3%, with very similar patterns noted in ER+30. In abduction of 0−90°, 5.8% of trials of superior and 85.3% of trials of inferior tendon achieved >3% strain. With passive ROM in SP, 26.5% of trials reached 3% strain in superior tendon compared to 100% in inferior tendon. Strain patterns in abduction and SP differed significantly ( p  < 0.001). Selective tenotomy and repair of the superior subscapularis tendon with open reparative or reconstructive shoulder procedures, when feasible, may be favorable for protected early passive ROM and rehabilitation postoperatively. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:518–524, 2016.